"Going Virtual Helped Me Learn That I Can Handle Everything": Campus Magazine Production as a High Impact Practice During the COVID-19 Pandemic. (December 2021) - Lance, Zoe L.; Reynolds, Chelsea J.
This case study documents a large, 4-year university magazine's transition to virtual instruction during the initial months of the COVID-19 pandemic. Using theoretical frameworks from Kuh's work on high impact practices (HIPs), this analysis offers empirical evidence that virtual student newsrooms may provide impactful learning experiences during crisis situations. Based on interviews, surveys, and newsroom observation, 23 magazine staff members reported improvements in their professional self-efficacy as they overcame logistics challenges and interpersonal hurdles similar to working media professionals. The case study also identifies strengths and weaknesses of crisis pedagogy. Implications for post-pandemic pedagogy and course planning are discussed.